PENERAPAN METODE KERJA KELOMPOK SERTA PENGARUHNYA TERHADAP HASIL BELAJAR SISWA KELAS VIII - Maria Sondang Triyuniati; Danang Budi Setyawan; Mudayat Mudayat (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
Learning and teaching activities at middle school in Biology subjects have low learning outcomes and students do not participate actively in learning activities. This is caused by monotonous learning in terms of learning methods and learning media. The problems that arise cause the need for classroom action research which aims to improve student learning outcomes in science (Biology) subjects by using group work methods and using more interesting learning media. Class action research was carried out in 2 cycles. The first cycle used the group work learning method by presenting the material they had prepared. After making a presentation, students were directed to discuss with each other and ask questions to their classmates. The average increase in student learning outcomes from pre-cycle to cycle I is 9.4414% from 70.35 to 73.15. The second cycle uses a group work learning method with a puzzle games method and students are directed to arrange and mark each part. After that, students discuss with each other in groups and explain it again in the puzzle results presentation session. Learning outcomes from cycle I to cycle II in table 2 experienced a drastic increase of 76.54103%% from 73.15 to 93.7.